Corneal keratocyte transition to mesenchymal stem cell phenotype and reversal using serum‐free medium supplemented with fibroblast growth factor‐2, transforming growth factor‐β3 and retinoic acid. (30th March 2017) - Sidney, Laura E.; Hopkinson, Andrew
Abstract: Keratocytes of the corneal limbal stroma can derive populations of mesenchymal stem cells (MSC) when expanded in vitro . However, once a corneal MSC (cMSC) phenotype is achieved, regaining the keratocyte phenotype can be challenging, and there is no standardised differentiation medium. Here, we investigated the transition of keratocytes to cMSC and compared different supplements in their ability to return cMSC to a keratocyte phenotype. Immunofluorescence and quantitative reverse transcription polymerase chain reaction demonstrated in vivo keratocyte expression of aldehyde dehydrogenase 3A1, CD34 and keratocan, but not any of the typical MSC markers (CD73, CD90, CD105). As the keratocytes were expanded in vitro, the phenotypic profile reversed and the cells expressed MSC markers but not keratocyte markers. Differentiating the cMSC back to a keratocyte phenotype using nonsupplemented, serum‐free medium restored keratocyte markers but did not maintain cell viability or support corneal extracellular matrix production. Supplementing the differentiation medium with combinations of fibroblast growth factor‐2, transforming growth factor‐β3 and retinoic acid maintained viability, restored expression of CD34, aldehyde dehydrogenase 3A1 and keratocan, and facilitated production of abundant extracellular matrix as shown by immunofluorescent staining for collagen‐I and lumican, alongside quantitative assays for collagen and glycosaminoglycan production. However, no differentiation medium was able to downregulate the expression of MSC markers in the 21‐day culture period. This study shows that the keratocyte to MSC transition can be partially reversed using serum‐free media and supplementation with retinoic acid, fibroblast growth factor‐2 and transforming growth factor‐β3 and can enhance this effect. This is relevant for development of corneal regenerative strategies that require the production of a keratocyte phenotype. Copyright © 2016 John Wiley & Sons, Ltd.